"Study on Nutrition Status and Urinary Tract Infection in Elderly People at Nursing Home" - J Nowroozi; A Mirgalili; K Pooshang Bagheri (Tehran University of Medical Sciences, 2004)
Malnutrition is a common problem among nursing home residents and encompasses adverse outcomes. This study was conducted to determine malnutrition and urinary tract infections as well as antibiotic resistance of isolated bacteria at Kahrisak nursing home in Tehran city, capital of Iran. Nutritional status was determined by direct detection of kitchen, checking the menue of weekly foods, quality and quantity of each meal for each person. The mean age of patients in this descriptive study was 77.2 years old, (ranging from 60 to 103). Samples of midstream urine from these patients were collected and bacteria were identified by standard bacteriological methods. Then, antibiotic resistance of bacteria was determined. On the basis of nutritional status, the quality and quantity of food for each meal was good and enough. From 520 samples of urine, bacteria were grown only from 81 samples. E. coli was the most common bacteria and the other bacteria were Proteus, Klebsiella, Staphylococci aureus, Alcaligenes faecalis, Pseudomonas aeruginosa and Providencia. All of bacteria were resistant at different rate to ampicillin, tetracycline, cephalothin and co-trimoxazol, but sensitive to ciprofloxacin and nitrofurantoin. Malnutrition in this study was less than 30%. This may be due to people helping, qualified foods, well nursing and suitable facility at Kahrizak nursing home.